The MMTV-Wnt1 murine model produces two phenotypically distinct subtypes of mammary tumors with unique therapeutic responses to an EGFR inhibitor - Adam D. Pfefferle; David B. Darr; Benjamin C. Calhoun; Kevin R. Mott; Jeffrey M. Rosen; Charles M. Perou (The Company of Biologists, 2019)
The Wnt gene family encodes an evolutionarily conserved group of proteins that regulate cell growth, differentiation and stem cell self-renewal. Aberrant Wnt signaling in human breast tumors has been proposed as a driver of tumorigenesis, especially in the basal-like tumor subtype where canonical Wnt signaling is both enriched and predictive of poor clinical outcomes. The development of effective Wnt-based therapeutics, however, has been slowed in part by a limited understanding of the context-dependent nature with which these aberrations influence breast tumorigenesis. We previously reported that MMTV-Wnt1 mice, an established model for studying Wnt signaling in breast tumors, develop two subtypes of tumors by gene expression classification: Wnt1-EarlyEx and Wnt1-LateEx. Here, we extend this initial observation and show that Wnt1-EarlyEx tumors exhibit high expression of canonical Wnt, non-canonical Wnt, and EGFR signaling pathway signatures. Therapeutically, Wnt1-EarlyEx tumors showed a dynamic reduction in tumor volume when treated with an EGFR inhibitor. Wnt1-EarlyEx tumors had primarily Cd49fpos/Epcamneg FACS profiles, but it was not possible to serially transplant these tumors into wild-type FVB female mice. Conversely, Wnt1-LateEx tumors had a bloody gross pathology, which was highlighted by the presence of 'blood lakes' identified by H&E staining. These tumors had primarily Cd49fpos/Epcampos FACS profiles, but also contained a secondary Cd49fpos/Epcamneg subpopulation. Wnt1-LateEx tumors were enriched for activating Hras1 mutations and were capable of reproducing tumors when serially transplanted into wild-type FVB female mice. This study definitively shows that the MMTV-Wnt1 mouse model produces two phenotypically distinct subtypes of mammary tumors that differ in multiple biological aspects including sensitivity to an EGFR inhibitor.